A year of experience with COVID‐19 in patients with cancer: A nationwide study. Issue 1 (27th November 2022) - Khosravifar, Mina; Koolaji, Sogol; Rezaei, Negar; Ghanbari, Ali; Hashemi, Seyedeh Melika; Ghasemi, Erfan; Bitaraf, Ali; Tabatabaei‐Malazy, Ozra; Rezaei, Nazila; Fateh, Sahar Mohammadi; Dilmaghani‐Marand, Arezou; Haghshenas, Rosa; et al.
Abstract: Background: Cancer is a major public health problem and comorbidity associated with COVID‐19 infection. According to previous studies, a higher mortality rate of COVID‐19 in cancer patients has been reported. Aims: This study was undertaken to determine associated risk factors and epidemiological characteristics of hospitalized COVID‐19 patients with cancer using a nationwide COVID‐19 hospital data registry in Iran for the first time. Methods: In this retrospective study, we used a national data registry of hospitalized patients with Severe Acute Respiratory Syndrome (SARS) symptoms and patients with confirmed positive COVID‐19 PCR between 18 February 2020 and 18 November 2020. The patients were classified into two groups patients with/without malignancy. Logistic regression model was utilized to analyze demographic factors, clinical features, comorbidities, and their associations with the disease outcomes. Results: In this study, 11 068 and 645 186 in‐patients with SARS symptoms with and without malignancy were included, respectively. About 1.11% of our RT‐PCR‐positive patients had cancer. In patients with malignancy and COVID‐19, older ages than 60 (OR: 1.88, 95% CI: 1.29–2.74, p ‐value: .001), male gender (OR: 1.43, 95% CI: 1.16–1.77, p ‐value: .001), concomitant chronic pulmonary diseases (CPD) (OR: 1.75, 95% CI: 1.14–2.68, p ‐value: .009), and presence of dyspnea (OR; 2.00, 95% CI: 1.60–2.48, p ‐value: <.001) were associated with increased mortality rate. Conclusion: Given the immunocompromised state of patients with malignancy and their vulnerability to Covid‐19 complications, collecting data on the comorbidities and their effects on the disease outcome can build on a better clinical view and help clinicians make decisions to manage these cases better; for example, determining special clinical care, especially in the shortage of health services.